The complete chloroplast genome sequence of Keteleeria fortunei (Pinaceae). Issue 2 (3rd July 2019) - Li, Yuanyuan; Zhang, Cheng; Zhang, Min; Li, Yongfu; Wang, Xianrong; Duan, Yifan
Abstract: Here, the complete chloroplast genome of Keteleeria fortunei, a vulnerable species in China, was sequenced by next-generation sequencing platform. Its circular genome was 117, 183 bp in length and the GC content was 38.5%. A total of 101 genes were annotated, including 4 rRNA genes, 20 tRNA genes, and 71 protein coding genes. This study would further our understanding of the genomics and the conservation and utilization of K. fortunei .